Communication profiles and sport experiences of collegiate track and field athletes - Pacewicz, C. E.; Smith, A. L. (Psychology of Sport and Exercise, 2023)
Objectives Athletes often communicate with one another and exchange information, attitudes, and feelings that can influence their sport experiences. In an effort to better understand the sport communication context, the purpose of the current study was to (a) describe communication profiles of athletes (b) examine potential predictors (i.e., team identity, sex) of profile membership, and (c) examine the salience of these profiles by assessing profile group differences on athletes` perceptions of burnout, engagement, satisfaction, and enjoyment.